Stabilitty indicating method development and validation for the quantification of chlorphenamine maleate related subtances using hplc technique - M. KARIKALAN; M.GNANA RUBA PRIYA; P. SHANMUGAPANDIYAN (International Journal of Pharma and Bio Sciences, 2016)
Chlorpheniramine Maleate (CPM) is an antihistamine used for the treatment of allergic disorders and common cold since, the method for determination of CPM related substances in pharmaceutical products is not described in current pharmacopoeias; the aim of this work was to develop and validate a precise, accurate and robust method. Separation was achieve on a RP C-18 column (250 x 4.6 mm, 5 µm particle size), column temperature kept at 40°C. The mobile phase content A: 80 volumes buffer solution (pH 3.00) and Mobile phase B 20 volumes of Acetonitrile, and UV detection wavelength at 225nm. The method was validated by ICH guidelines and validation studies proved that the method is stability indicating and used for determination of related substances of CPM tablets.